INTRASPECIFIC VARIATIONS OF 16S MITOCHONDRIAL GENE SEQUENCES OF YELLOW RICE STEM BORER,scirpopbaga incertulas (LEPIDOPTERA: CRAMBIDAE) FROM WEST JAVA - RIKA RAFFIUDIN; RUTH MARTHA WINNIE; I MADE SAMUDRA (SEAMEO BIOTROP, 2011)
Yellow rice stem borer (Scirpophaga incertulas) is one of the most important rice pest insects in Asia, including Indonesia. However, there is a lack of genetic data for this important agricultural insect. Therefore, this study was conducted to explore intraspecific differentiation of S. incertulas partial 16S mitochondrial gene from Bogor, Karawang, Indramayu and Cirebon (West Java, Indonesia). Here, we reported a total of 325 bp of 16S mitochondrial gene of S. incertulas from the obtained samples. Among all DNA sequences, three haplotypes of 16S mitochondrial gene were observed and submitted to GenBank under Accession Number of GU191881, GU191882, GU191883, respectively for haplotype 1, 2, and 3. The haplotype 1 was found in all S. incertulas surveyed locations, except Bogor. The haplotype 2 and 3 were found only in from Cirebon and Bogor samples. These haplotype variations can be applied as DNA markers for S. incertulas early larva detection method among other rice stem borers. Hence, further explorations of the mitochondrial variations of S. incertulas in Java and other parts of Indonesia are needed. Keywords: moth, haplotypes, genetic differentiations, molecular identification